Strategi Kampanye Arif Hamid Rahman dalam Mendapatkan Dukungan dari Anggota Persatuan Islam (PERSIS) pada Pemilihan Anggota Legislatif Jawa Barat tahun 2019 - Nurunnisa, Rizkya; Djuyandi, Yusa (Journal of Social and Policy Issues, 2023)
The 2019 election has captured the interest of the majority of Indonesians, particularly the dynamics and escalation of the presidential contest, in which supporters criticize each other's presidential candidates. The political symptoms that were plainly obvious, especially during the pre-campaign period, were the strengthening of political propaganda such as identity politics, particularly those related to religion. Arif Hamid Rahman, a Gerindra party cadre as well as a Persis cadre who ran for the West Java Provincial DPRD election in 2019, used community and youth organizations as tools in his success. This study was conducted in West Java Electoral District 1, specifically the cities of Bandung and Cimahi, with the goal of determining how Arif Hamid Rahman's campaign strategy to the Persis organization worked. By employing a descriptive qualitative research method to explain the phenomenon of the campaign strategy implemented using Pawito's campaign strategy theory, which includes segmenting, positioning, branding, and media strategy, as well as deepening each data and source in the form of interviews with relevant informants, documents, and reports that have a correlation with the campaign strategy implemented by Arif Hamid Rahman to gain support from members of the public. According to the findings of this study, Arif Hamid Rahman carried out each stage of the campaign strategy dimensions in accordance with Pawito's theory.